Health Promotion Modeling Practices among School Teachers in Nepal - Aryal, Bhagwan; Sharma, Tribhuwon; Pokhrel, Mahesh; Joshi, Bhagarathi (International Research Journal of MMC, 2024)
Modeling enhances client understanding by creating a visual representation of their world, promoting facilitation, nurturing, and unconditional acceptance within their framework and perspective. The study investigates secondary-level teachers' practice of modeling skills in classrooms for student health promotion, focusing on Nepalese schools and considering the modeling constructs from the "modeling and role modeling theory." The study utilized a cross-sectional survey design with a descriptive quantitative approach, involving questionnaires distributed to secondary school teachers in three districts, Chitwan, Bhaktapur, and Rasuwa in 2018. Of the 1611 teachers, a total of 414 teachers were reached out for the self-administered structured questionnaire. The final sample size was 344 teachers with a response rate of 83.09%. The tool was made inclusive, evaluated for face validity, and maintained confidentiality and anonymity during data collection and presentation. The data were analyzed using descriptive statistics and statistical significance was set at p < 0.05. The study found that teachers performed three categories of modeling for students' health: facilitation, nurturance, and unconditional acceptance. Those activities helped teachers understand their students' perspectives and realize their health situation. However, only 6.1% of teachers provided healthy experiences, 11.5% cared for students' health needs, and 34% performed unconditional acceptance. Persuasive techniques like facilitation, nurturance, and unconditional acceptance are crucial for strengthening persuasion and encouraging appropriate behaviors among the students. Authorities should conduct refresher training for teachers to promote these skills, as they are not reflected in real classroom situations. Further research is recommended to understand the causes of this discrepancy.